MODEL PROBLEM BASED LEARNING (PBL) BAHAN KIMIA DALAM MAKANAN UNTUK MENUMBUHKAN POLA MAKAN SEHAT - Mulia Susanti (LPPM Universitas Pekalongan, 2014)
The research is conducted based on high number of intoxication at school due to student’s low understanding on the negative effects of additives substance in food. Therefore it is needed a learning models that can improve the understanding of additives substance in food. The formulation of the problem posed is effectiveness this models to improve student learning outcomes and to foster healthy eating. The purpose of the study is to analyze the effect of problem- based learning towards the refinement of cognitive learning outcomes and to foster healthy eating. This reseach conducted on class VIII SMPN 1 Kota Tegal consists of two classes taken at random from the seven classes, one class as a control group and another as an experimental group. The PBL models is effective showed by students who learning mastery > 85%, and positive effect on students' perception of healthy eating by 97,47%. Data correlation on cognitive learning outcomes and students' positive perceptions of healthy eating show at 0,689 with significance value of 0,01<0,05 which means the instructional model of PBL can foster healthy eating in students. Key words: chemical substances in food, healthy eating, problem based learning